ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL FUNGSI KOMPOSISI - Pipin Trianingsih; Noerhasmalina Noerhasmalina; Binti Anisaul Khasanah (Universitas Muhammadiyah Metro, 2022)
There are still many students who have errors in solving math problems, namely the composition function. This study aims to describe the average percentage of students who make mistakes in solving compositional function questions and to describe the criteria for student error rates based on the types of errors, namely conceptual, principle, and operational errors. This type of research is qualitative research. The research subjects were students of class XI Accounting at SMK Muhammadiyah 1 Pringsewu with the object of research being student errors in solving math problems. Data collection techniques using tests and interviews. The analysis in this study uses the percentage technique, and the validity of the data using triangulation techniques. The results of this study indicate that students make conceptual errors of 43% on the medium criteria, the principle error of 44% on the medium criteria, and 60% operating errors on the high criteria.